Good Corporate Governance Bank Syariah di Indonesia - Ahdiyat Agus Susila (Iqtishodiyah : Jurnal Ekonomi dan Bisnis Islam, 2019)
In Indonesia, the principles of GCG implementation are regulated in the General Guidelines for Good Corporate Governance in Indonesia by the National Committee on Governance (KNKG). This general guideline is a reference for companies to implement GCG in order to encourage the achievement of company sustainability through management based on the principles of transparency, accountability, responsibility, professionalism, and fairness.